Factors Influencing Nurses’ Skills in Managing Resuscitation Patients: A Systematic Review and Meta-Analysis - Fariz Jauhar Muslim (SOSMANIORA: Jurnal Ilmu Sosial dan Humaniora, 2025)
Cardiac arrest remains a major global health concern, and nurses' ability to perform effective cardiopulmonary resuscitation (CPR) is critical to patient survival. However, significant variations in CPR skills among nurses have been widely reported, influenced by factors ranging from individual characteristics to institutional support. This study aimed to systematically identify and analyze the factors influencing nurses’ competence in performing CPR. A systematic literature review and meta-analysis were conducted in accordance with PRISMA guidelines, utilizing databases such as PubMed, ScienceDirect, Springer, and Google Scholar to identify relevant articles published between 2021 and 2025. Ten studies met the inclusion criteria and were appraised using the JBI Critical Appraisal Checklist. The results indicated that knowledge, education, training, retraining, work experience, situational awareness, work environment, body mass index (BMI), and psychological factors contribute to variations in CPR proficiency. Nevertheless, the pooled meta-analysis revealed a very small and statistically insignificant effect size (0.0665; 95% CI: -0.0464 to 0.1794), with moderate heterogeneity (I² = 57.5%). Subgroup analysis showed that structured training had a more substantial positive effect compared to work experience. These findings suggest that experience alone is insufficient to ensure CPR competence. Therefore, standardized, recurrent training aligned with international guidelines and supported by adequate clinical infrastructure is essential to enhance nurses' resuscitation skills and improve emergency care outcomes.